When Travel Meets Tourism: Tracing Discourse in Tony Wheeler's Blog - Azariah, Deepti (Taylor and Francis, 2011)
This paper examines a guidebook publisher's travel blog in order to shed light on the tensions between discourses of travel and tourism. Tony Wheeler's Blog is written by the founder of Lonely Planet and is hosted on the company's website. I argue that the “blog” title implies that the text has certain intrinsic qualities, some of which are evident while others are not. I also argue that this text is an online travel narrative that draws on the discourses of travel, tourism, and blogging itself. Travel and tourism are often seen as conflicting, and the traveler–tourist dichotomy has found expression in various travel-related narratives. So Tony Wheeler's Blog becomes a site of negotiation between the discourses of travel and tourism, and in so doing takes on certain aspects of the blog while omitting or only imitating others.